Dispute Settlement Mechanism In Bilateral Investment Treaties (BITs) - Yetty Komalasari Dewi; Arie Afriansyah (Universitas Airlangga, 2019)
The Bilateral Investment Treaty (BIT) or in Indonesia known as “Perjanjian Promosi dan Perlindungan Penanaman Modal (P4M)” contains a very powerful dispute settlement mechanism that allows investors to file a lawsuit directly against a host country allegedly violating investment protection under international law. This is known as Investor-State Dispute Settlement (ISDS). The ability of investors to “impose” their rights directly against a country without the existence of an arbitration clause is considered as one of the extraordinary achievements of the BIT innovation. This paper discusses two types of dispute resolution models contained in almost all BITs signed by Indonesia, namely State-State Dispute Settlement (SSDS) and Investor-State Dispute Settlement (ISDS). It also elaborates the weaknesses of the current dispute resolution formula, especially in the ISDS clause and provides the possibility of improvements to the formulation of the ISDS clause to better ensure a balance between the protection of foreign investors and the needs of the host country.